The Feasibility and Patient Acceptance of a Treatment Support Group in the Dialysis Setting - Haliburton-Rudy, Dawn; Stockard, Julie A.; Anderson, Pamela (The Journal of Nephrology Social Work, 2011)
A structured treatment support group was conducted with 2 caregivers and 6 people on dialysis who reported feelings of isolation and episodic non-psychotic depression. The patients were medically diagnosed with end-stage renal disease and are currently undergoing in-center hemodialysis for their treatment modality. Participants in the group were recruited on a volunteer basis from 4 DaVita Dialysis clinics located in Fountain and Colorado Springs, CO. The facilitating social workers utilized cognitive behavioral therapy and relaxation breathing techniques for the group. Self-reports were utilized to measure the successful outcomes of the group. The reports indicate that patients perceive group therapy in the dialysis setting positively, and that it is feasible to conduct group therapy in the dialysis setting.